Exploring into Graduate Research Term Papers: a Quest for Generic Disciplinary Tendencies - Darani, Parviz Ahmadi; Tahririan, Mohamad Hassan; Afghary, Akbar (Research in Language, 2018)
The purpose of this exploratory analysis was to capture students’ generic tendencies in the organization of original research term papers written by graduate within the same linguistic, cultural, and disciplinary territory. A model proposed by Sheldon (2011) was benchmarked against a corpus of 60 English research term paper introductions to identify the saliency of move schemes along with step and sub-step realizations. At step-level analysis, the proportion of the various steps within Move 2 (indicating a gap, adding to what is known, and presenting positive justification) exhibited a pervasive lack of rhetorical tendency that contradicted the previous genre-based findings. Such an exploration, offers implications for English for research publication purposes instruction and academic literacies based on academic conventions and norms.